(3JgPjH GdhUhds - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3Ydj Hf YHO Gddg hjQOjs)
(3ChdgG (B:s
(3GdMeO ddg QGaY OQLGJ GdYGQajf(B... (3CeG HYO, agPG cJGH (B... (3MQQJ ajg WQb GdCMcGe Ydi GdELeGd ef ZjQ JWhjd hdG ENdGd(B...s
(3BNQgG (B:s
(3aEf UQM GdeYJQV HGdaQb Hjf GdCUd hGdaQY hLH Ydjg HjGf (B... (3CeG HefY hLhO GdCUd hGdeWGHbI HJCKjQg(B... (3EeG HfU Ch ELeGY(B... (3hdcf gPG BNQ eG fPcQg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B284s
(3EjVGM Gdecfhf(B: (3L(B1(3, U(B342s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs